“I Want to Be Born with That Pronunciation”: Metalinguistic Comments About K-Pop Idols’ Inner Circle Accents - Jihye Kim; Luoxiangyu Zhang (Languages)
The Korean popular music (K-pop) industry, with its global popularity and increasing multilingual orientation, serves as a suitable context for exploring language perceptions. This research examines the metalinguistic commentary on K-pop idols’ English accents on YouTube. Specifically, we investigate how online users evaluate the idols’ English accents and how their metalinguistic comments communicate linguistic ideologies that favor a “native” way of speaking. Our dataset consists of 602 metalinguistic comments drawn from four popular YouTube videos featuring the evaluation of K-pop idols’ accents. We employ content analysis to first categorize comments into positive, negative, and neutral evaluations, then focus on aspects being evaluated in the users’ comments (e.g., social attractiveness and (non-)nativeness). The results indicate that a vast majority of comments (88.1%) convey positive evaluations, largely associating the idols’ accents with social appeal and native-like accents. Although a few neutral and negative evaluations exist, our result shows a dominant preference for inner circle accents and complex attitudes toward accented speech in digital spaces. We conclude by highlighting the influence of digital platforms in shaping language perceptions and the implications for linguistic stereotyping in the context of K-pop culture.